Approximations to distribution of median in stratified samples - Čiginas, Andrius; Rudys, Tomas (Lietuvos matematikos rinkinys, 2011)
We consider an Edgeworth type approximation to the distribution function of sample median in the case of stratified samples drawn without replacement. We give explicit expression of this approximation, and also its empirical version based on bootstrap. We compare their accuracy with that of the normal approximation by numerical examples.
Keywords: finite population; stratified sample without replacement; Hoeffding decomposition; Edgeworth expansion; bootstrap